THE INFLUENCE OF NIOBIUM ON THE ACIDITY AND STRUCTURE OF GAMMA-ALUMINA-SUPPORTED VANADIUM OXIDES - Sathler,M.N.B. (1998)
Gamma-alumina-supported niobium oxide was used as a support for vanadium oxides. The influence of the addition of niobium oxide was studied by looking for changes in the structure and acid-base character of superficial species. Vanadium oxide was deposited using the continuous adsorption method; niobium oxide was impregnated using the incipient wetness method. The catalysts were characterized by XPS, UV-visible and IR spectroscopy. Catalytic tests were performed using propane oxidation reaction at 400oC. For coverage below the monolayer, both vanadium and niobium oxides were observed in slightly condensed superficial species. The presence of vanadium oxide on the support was found to increase the Lewis acidity and create some Bronsted acidity. Higher catalytic activity and selectivity for propene were associated with vanadium oxides. The presence of niobium did not contribute to the modification of the chemical properties of superficial vanadium but did decrease the adsorption of vanadium on the alumina.